The Effect of Blocks Constructive Game to Improve Children’s Fine Motor Skill in the Year of 4-5 Years Old - Islammeiliani, Dinna; Khamidun, Khamidun (BELIA: Early Childhood Education Papers, 2017)
Fine motor skills of children has an important relation in their daily life, such as writing, shaping, grasping spoon, tying shoes, and buttoning clothes. Those skills will be perfect if there was a stimulation. The stimulation can be given by providing some learning method such as blocks constructive games. By providing a game as a learning method, it can make the children happy. The objective of this research was to find out whether there was an effect of constructive game in developing children motoric skills of ages 4-5 years. This research used experiment method of Pre-experimental and One Group pretest and posttest design. Research subject were children of 4-5 years, group A in TK Pembina ABA 54 Semarang. Purposive sampling was used to take the sample. Paired Sample t-Test was used to analyze the data. Posttest result of experiment group showed higher score than pretest. The measurement of paired sample t-Test aimed the t -42.003 with the sig (2-tailed) <0,05. The research aimed 100% as an amount of the effect by using constructive blocks game to improve children fine motor skill. There were a significant difference between the fine motor skill after and before conducting the constructive blocks game.